2011
DOI: 10.1016/j.jpeds.2010.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum Caffeine Levels and Changes in Cytokine Profile in a Cohort of Preterm Infants

Abstract: Objective To determine changes in cytokine levels associated with caffeine treatment in a cohort of preterm infants. Study design For this observational prospective study, we collected clinical data from 26 preterm infants (≤30 weeks gestational age). In addition to caffeine levels, cytokine profiles in peripheral blood (PB) and tracheal aspirates (TA) were determined with enzyme-linked immunosorbent assay at birth, before and after (at 24 hours and 1 week) initiation of caffeine. Non-parametric statistics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 50 publications
3
37
0
1
Order By: Relevance
“…A loading dose (10 mg/kg BW) and maintenance dose (5 mg/kg, q24 h BW) resulted in the target serum level range of 10-20 µg/ml [7]. Within this range, in preterm infants serum caffeine levels have a U-shaped correlation with cytokine profiles [18]. Furthermore, in a recent randomized controlled trial, higher doses of caffeine (40 mg/kg BW followed by 20 mg/kg BW and 10 mg/kg BW always after 24 h) were associated with a higher incidence in neurological impairment (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A loading dose (10 mg/kg BW) and maintenance dose (5 mg/kg, q24 h BW) resulted in the target serum level range of 10-20 µg/ml [7]. Within this range, in preterm infants serum caffeine levels have a U-shaped correlation with cytokine profiles [18]. Furthermore, in a recent randomized controlled trial, higher doses of caffeine (40 mg/kg BW followed by 20 mg/kg BW and 10 mg/kg BW always after 24 h) were associated with a higher incidence in neurological impairment (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…cerebellar hemorrhaging) and alterations in motor performance [22]. The effects of caffeine can be both anti- and proinflammatory, depending on the serum concentration [18]. In a cohort of preterm infants, it has been demonstrated that higher serum caffeine levels (≥20 μg/ml) were associated with an increase of proinflammatory cytokines such as TNF-α, IL-1 and IL-6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A relationship between serum caffeine levels and cytokine concentrations was already observed in tracheal aspirates and peripheral blood of preterm infants (9). For low serum caffeine levels, concentrations of proinflammatory cytokines TNF-␣, IL-1, and IL-6 were reduced, but increased at higher levels, which could contribute to the severity of inflammatory conditions such as development of BPD (24).…”
Section: Discussionmentioning
confidence: 84%
“…Other protective mechanisms of caffeine in this regard are supposed to be anti-inflammatory actions (14), which include inhibition of proinflammatory cytokine production (9,29).…”
Section: Discussionmentioning
confidence: 99%